2004
DOI: 10.1016/j.visres.2003.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse luminance flicker increases blood flow in major retinal arteries and veins

Abstract: It has been shown that diffuse luminance flicker increases optic nerve head blood flow. The current study has been performed to quantify changes in retinal blood flow during flicker stimulation. In a group of 11 healthy volunteers, red blood cell velocity and retinal vessel diameters were assessed with bi-directional laser Doppler velocimetry and the Zeiss retinal vessel analyzer before, during and after stimulation with diffuse luminance flicker. Retinal blood flow was calculated for each condition. Flicker s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
82
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 12 publications
6
82
1
1
Order By: Relevance
“…This is in good agreement with human data indicating that most of the vasodilator response occurs in the microvasculature. 58 A reduction in the retinal response to flicker stimulation can be seen in diabetic patients before any change in pattern electro-retinography becomes evident. 59 In diabetic rats, the abnormal retinal flicker response can be normalized by inhibition of inducible nitric oxide synthase.…”
Section: Discussionmentioning
confidence: 99%
“…This is in good agreement with human data indicating that most of the vasodilator response occurs in the microvasculature. 58 A reduction in the retinal response to flicker stimulation can be seen in diabetic patients before any change in pattern electro-retinography becomes evident. 59 In diabetic rats, the abnormal retinal flicker response can be normalized by inhibition of inducible nitric oxide synthase.…”
Section: Discussionmentioning
confidence: 99%
“…Manganese ions are likely localized in the intracellular space of the retinal pigment epithelium and the endothelial cells outlining choroidal vessels, which are unlikely to differ between light and dark conditions. Choroid BF is generally unresponsive to visual stimulation, and light and dark adaptation as detected by using laser Doppler flowmetry techniques in humans, 42 although exception has been noted. 3 Others have also suggested that choroid is not regulated by local metabolic controls.…”
Section: Discussionmentioning
confidence: 99%
“…Other functional imaging techniques of the retina include intrinsic optical imaging, 47 laser Doppler flowmetry, 42 laser speckle imaging, 48,49 and depth-resolved functional optical coherence tomography. 50,51 Intrinsic optical imaging measures reflectance associated with visual stimulation, albeit without laminar resolution.…”
Section: Discussionmentioning
confidence: 99%
“…30 In humans, a flickering light results in blood flux increases of 30-38% in the optic nerve head 31,32 and flux increases of 59% in retinal arterioles. 33 In the cat optic nerve head, flux increases of 27-59% are observed. 27,34 As originally noted by Roy and Sherrington, 20 the localized nature of blood flow control is a hallmark of the functional hyperemia response.…”
Section: Introductionmentioning
confidence: 99%